Parental Dominance in Early Marriage in Anreapi District, Polewali Mandar Regency: Analysis of Maqashid al-Sharia - Arman, Arman; Rusdi, M Ali; Muchsin, Agus (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
Early marriage is often the subject of parental domination in cultures and societies that uphold strong traditions and norms. This article analyzes this phenomenon by using the Maqasid Sharia framework as a basis for understanding the implications of parental domination in the context of early marriage. The research method used is descriptive qualitative research, with normative and juridical approaches to explore the relevant aspects of Islamic law and values. The research involved in-depth interviews with a number of couples who experienced parental dominance in the early marriage process. The analysis shows that parental domination often contradicts the humanitarian and welfare principles of Maqasid Sharia. While it may be legally valid, this domination can result in an imbalance of power in the marriage relationship, causing conflict and dissatisfaction among young couples. Through a normative approach, this research highlights the need to return to the principles of equality, justice and freedom that underpin the institution of marriage in Islam. The juridical approach examines relevant aspects of the law and emphasizes the importance of integrating maqasid values into the practice of Islamic law.